Study on the safety and effectiveness of low-dose vs. regular-dose fondaparinux in preventing venous thromboembolism prophylaxis following total knee arthroplasty - Chen, Ping-bo; Wang, Jing; Wang, Lei; Xiong, Shou-liang; Wang, Chao; Yang, Xin; Li, Cong-ming; Wang, Qiang; Zhang, Yin-chang (Frontiers in Cardiovascular Medicine, 2023)
Background: This study aims to evaluate the effectiveness and safety of low-dose (1.5mg) fondaparinux for venous thromboembolism (VTE) prophylaxis in patients post-total knee arthroplasty (TKA).Methods: We retrospectively identified 314 patients who carried out the primary TKAs and received fondaparinux for VTE chemoprophylaxis between July 2020-December 2021. A total of 141 TKA patients were excluded according to the exclusion criteria. Two groups of patients were established: the low-dose group included 84 patients who injected 1.5 mg of fondaparinux, and the regular-dose group included 89 patients who injected 2.5 mg of fondaparinux. The pre-operative blood analysis and coagulation assays were performed. The surgical time, the incidence of symptomatic VET, blood loss, wound complication, bleeding, drainage, and mortality of patients were determined and assessed.Results: The pre-operative blood analysis, body mass index, sex, age, and coagulation assays of patients in both groups were comparable. In terms of symptomatic pulmonary embolism and deep vein thrombosis, there was no significant difference (variation) between the two groups. However, patients in both groups showed a substantial difference in terms of blood loss, drain volume, wound complication, and transfusion rate.Conclusion: In prevention of VET in patients post-TKA, low-dose fondaparin is as effective as conventional dose fondaparinux. A significant decrease in blood loss, post-surgical transfusion rates, and wound complications were detected in patients given low-dose fondaparinux compared to those receiving regular-dose fondaparinux.